Mental Health Among High School Students: A Comparative Study Based on Gender and Schooling Type - Mallika; Suresh S. Sammasagi (Journal of Psychology and Social Sciences, 2026)
Adolescent mental health is a critical determinant of psychosocial adjustment and academic achievement. This study aimed to examine the level of mental health among high school students and analyze differences based on gender and type of schooling (residential vs. non-residential). A quantitative causal-comparative research design was employed involving 200 high school students (100 boys and 100 girls; aged 14–16 years) selected via convenience sampling from schools across Karnataka, India. Data were collected using the standardized Mental Health Battery (MHB) developed by Singh and Sen Gupta, which evaluates multiple dimensions of mental health with established reliability (α = 0.72–0.87). Data were analyzed using descriptive statistics and independent samples t-tests. The descriptive findings revealed an alarming prevalence of psychological vulnerability, with 61% of students falling into poor (47%) and very poor (14%) mental health categories, while only 1% demonstrated good mental health. Inferential analysis indicated significant gender differences, with female students exhibiting significantly higher overall mental health scores than male students (t = 2.88, p = .004). Furthermore, residential school students demonstrated significantly superior mental health compared to their non-residential peers (t = 5.46, p = .001). These findings underscore the protective nature of structured educational environments and highlight the urgent necessity for targeted, school-based mental health interventions and institutional counseling frameworks tailored to adolescent boys and day scholars.